Reparative effect of different dietary additives on soybean meal-induced intestinal injury in yellow drum (Nibea albiflora) - Ma, Shipeng; Wang, Ligai; Zeng, Yanqing; Tan, Peng; Chen, Ruiyi; Hu, Weihua; Xu, Hanxiang; Xu, Dongdong (Frontiers in Immunology, 2023)
Soybean meal (SBM) is an acceptable replacement for unsustainable marine fish meal (FM) in aquaculture. However, we previously reported that high dietary SBM supplementation causes intestinal inflammatory injury in yellow drum (Nibea albiflora). Accordingly, a 4-week SBMinduced enteritis (SBMIE) in yellow drum trial was conducted first, followed by a 4-week additive-supplemented reparative experiment to evaluate the reparative effect of five additives on SBMIE in yellow drum. The control diet comprised 50% FM protein substituted with SBM. The additive-supplemented diet was added with 0.02% curcumin (SBMC), 0.05% berberine (SBM-BBR), 0.5% tea polyphenols (SBM-TPS), 1% taurine (SBM-TAU), or 0.8% glutamine (SBM-GLU) based on the control diet, respectively. The weight gain (WG), specific growth rate (SGR), feed efficiency ratio (FER), and survival rate (SR) of fish fed the additive-supplemented diets were significantly higher than those of fish fed the SBM diet. The WG, SGR, and FER of fish fed the SBMC, SBM-GLU and SBM-TAU diets were significantly higher than those of fish fed other diets. Moreover, fish fed the additive-supplemented diets SBMC and SBM-GLU, exhibited significantly increased intestinal villus height (IVH), intestinal muscular thickness (IMRT), and intestinal mucosal thickness (IMLT) and significantly decreased crypt depth (CD) in comparison with those fed the SBM diets. The relative expression of intestinal tight junction factors (ocln, zo1), cytoskeletal factors (f-actin, arp2/3), and anti-inflammatory cytokines (il10, tgfb) mRNA was remarkably elevated in fish fed additive-supplemented diets than those of fish fed the SBM diet. Wheras, the relative expression of intestinal myosin light chain kinase (mlck) and proinflammatory cytokines (il1, il6, tnfa) mRNA was markedly lower in fish fed the additivesupplemented diets. The highest relative expression of intestinal ocln, f-actin, and arp2/3 and the lowest relative expression of intestinal mlck were found in fish fed the SBMC diet. Hence, all five dietary additives effectively repaired the intestinal injury induced by SBM, with curcumin exhibiting the strongest repair effect for SBMIE in yellow drum.